Adolescence: A Period of Transition - Landmark, Leena Jo; Geye, Trina (Journal of the American Academy of Special Education Professionals, 2014)
Because of the important role secondary special educators have in the transition to adulthood of adolescents with disabilities, it behooves educators to have an understanding of human development. The lifespan perspective on human development is particularly relevant to transition planning. Individuals with a lifespan perspective believe development to be lifelong, multidimensional, multidirectional, and plastic (Baltes, Reese, & Lipsitt, 1980). By viewing transition planning through a lifespan developmental lens, educators are able to enhance the transition process and more comprehensively prepare their students with disabilities for adulthood. This article describes how the lifespan perspective impacts transition planning and provides an illustration of how a special education teacher can use this framework to develop a student’s transition portions of the Individualized Education Program.